Implante Coclear: estudos concernentes à biopolítica, ao biopoder e ao biocapital em III volumes - Garcia, Eduardo de Campos (2015)
This thesis, though apparently deals with issues concerning the Cochlear Implant, its object collides an analysis than visuoimperceptual order authorizing the operation of body modification involving the overlapping between man and machine: the creation of discursive clinical language, legal and biological order in interpersonal plots and by the person who declares itself cyborg bionic ear and ends up involved the idea of the formation of other identities and their own community. In proposing think of other identities, often subjetivadas by the person with a cochlear implant, you need to list their bifurcations in power of the territory: implanted deaf, implanted, people with cochlear implants, and cyborg cyborg bionic ear. All make up the group calling itself: cyborg community. It is through the finding of groups / systemic communities it was possible to understand that there is the relationship established between the cyborgs people bionic ear, a kind of aesthetic link that feeds the need for man-machine hybridization simplifying it in the form of an identity: cyborg. What is here explained has the daily visitations basis, within 2 years, the three communities formed by cyborgs people bionic ear and their families and its members people from all states of Brazil and some other countries like Argentina, Chile, Mexico, Uruguay and Portugal. Depending on the complexity of its content, because all it takes as its starting point the deaf person and deafness as creation of cultural industry normality / abnormality, moves through the repaired subject and all the power that sustains the discourse of rehabilitation, and arrives in subject cyborg bionic ear as clinically object created in the economic political needs of the biotechnology industry. Therefore, this thesis is not only to analyze the subject of relationship that had altered their bodies through intraorgânica technology, but the whole language game and power that surrounds him and the deaf or implanted person subjectivizing. There is a performative game that includes in its plot and advertising rule, creative instances of persuasion, design and cyborg body, shape and condition, repetitive stories and promises of healing and rehabilitation under the justification of advances for / improvements in the body. The person subjected to this discursive scheme / language succumbs to its intention: to produce a new concept of body parts made up of organic and inorganic parts, living matter and dead matter. The subject of the situation, hereinafter called bionic ear cyborg is, among other possibilities when analyzed, a result of what Michel Foucault (1926-1984) sought to explore how biopolitics and biopower and consequently, although it has not been explored by him directly because it is a concept that comes into play in contemporary times, the biocapital. The heart of the matter involving the prefix "bio" and that makes up the concepts of biopolitics, biopower and biocapital, is anchored in antiquity. It is with Giorgio Agamben (1942-) as someone who explores the theory of Michel Foucault, in his book Homo Sacer, I seek the root of the three words presented. Agamben (2010) talks about two contemporary concepts: naked life and Bios. Bare life is a Greek concept, which he said is a life unworthy of being lived, banished, worthless, who lives adrift and at the mercy. To her, the accident belongs. Bios is another concept and differs from bare life because you are subscribed ordination of legal and political life. It is under supervision of the State and it is marked in that it fits the prescribed conditions. The right of citizens is a mark of the juridical and political life. His duties also. Understanding these issues can seem complex at first glance, and are. But it can also be understood as the foundation of society and its control devices. The bare life is always the leaking of this pre-announced control. Meets and resembles the concept of "left" and / or non-identical. Based on the concept of bare life and bios, biopolitics, biopower and biocapital are devices that demarcate stocks having power / control over them. The order of the speech that forms the deaf, although protected by law 10.436 / 2002, and people who choose or are submitted to cochlear implantation can be interpreted as bare lives because they are reduced to certain moral judgment and as a result are allocated so "liability" in the decisions that capture them. Most of the time, and often, public policies that should safeguard and protect citizens when it comes to the deaf and bionic ear cyborgs, the fragility of state protection becomes your brand. But this is a function, first, of biopower: score. His authority is above all a kind of spirit in the form of identity that, to the extent that subjectivizing, marks, orders and defines the location of where and how the subject can and how and when to speak. Bionic ear cyborgs has its demarcation in social relations: they are a priori hybrids. The deaf, deafness, the cyborg bionic ear and the listener are nomenclatures / or are supported by the state or banned for life that is in the legal and political domain. Although the "legal" word make mention of legal issues, its genesis collides with the construction of judgment, almost always or most of the time, the creation of clinical language. It is made clinically by language production that normative and functional identities became rule in interpersonal relationships since the nineteenth century - as can be seen in the writings of Michel Foucault (op.cit.), See the condition of normality and abnormality prescribed and commissioning scene by the medical encyclopedia over the nineteenth and twentieth centuries. In this view, Foucault (op.cit.) And Canguilhem (1904-1995) agree. Under the control perspective, biopolitics, biopower and biocapital, although related, are power developments. In descending order, the twenty-first century living a body that is authorized legal and political order to be changed, and consequently calls an identity for himself, his nomination as bionic ear cyborg meets an order for layout of control over your body. Biocapital is the registered life, in the form of biological capital, made product and / or thing, but that is under state control to the extent that this is liberalism itself too much. The supply and demand in the market, now is related to the reconfiguration of the body. As stated by a mother, responsible for choosing the implementation of intraorgânico device in his son stayed until the end of life is linked to a company that charges all you want to do to my son's ear maintenance. Sometimes even have part because they take a particular line model and do not produce more. Maintenance is expensive and I was fortunate enough to win the process that determines that its costs are covered by the health plan. The SUS also deploys, but the quality is much lower. Anyway, even if it is not well defined laws that guarantee the right of people with cochlear implants to a quality product and to ensure the achievement of "healing", the market defines their daily lives to the extent that causes a relationship between company and consumer . In this sense, the bionic ear cyborg is proposed to be by analogy interpreted as Naked Life. As we observed, waiting among many other things, their place in society as something defined and to enable it to institutional representation in political territory. Although the bionic ear cyborg is a reality in contemporary society, its symbolic capital is under construction because even their condition as a person remains in an interstitial zone: is a human machinic and / or a humanized machine. Obviously the search for a possible definition was not simple, but the thesis shows that people submitted to cochlear implantation relate to each other calling themselves cyborgs. For them, cyborg is the means by which to define an improved body technology. Principle bumps into international agreements and economic interests and market. However, the biocapital or its provocations in control of the territory would not be active if every one share of biopower had not been articulated since the nineteenth century and perfected in its secular path, the twenty-first century. Biopower, on behalf of human subjectivity, throughout the twentieth century sought to wage a battle of social classes, governance schemes, identity struggles: superficial and violent. Created truths and through them has measured judgments, imposed a moral to each and every body at the level of sex, gender, race and nature. Positive science advancing in the twentieth century, proposed thinking about life and its existence from the perspective of the classifications and as a result made it possible for the identity of each were elevated to group category condition: these under the biopower field were prescribed according to heredity, the economic reality and territorial cohesion and united under the imaginary tie their community. The state ideological apparatuses (as proposed by Althusser 1918-1990) tried to teach and keep alive the language for the creation of identical; of the difference does not escape. All the difference, as pointed out by the thesis, is a negative demarcation when related to identity matrix, but is also the hint and demarcation of an "identity other" when grouped in community. The biopolitics, biopower and biocapital, in short, are the domain of strength which I propose be understood as visuoimperceptual. It takes away the autonomy giving the impression of working through it. Deaf, listeners, natural deaf and cyborgs of bionic ear (people with cochlear implants) are triangular and visuoimperceptual this game. They compete for the podium of reason and try, each with their arguments, to convince that their way of life is in the order of reason, the best choice, of human evolution. At the bottom of a bottomless pit when digging to find answers what lies are layers and layers of identity. They overlap in the form of conquest, but say nothing about the person who embodies. What remains, as can be seen after reading and analyzing, numerous threads of groups on the social network formed by people with cochlear implants and their families, seems to be the anguish, disappointment, fear (when the cochlear implant does not work). However, you could not think of biocapital and biopower in the late nineteenth century life had not been entered in the state control: Governance Act. The biopolitics is the skeleton that supports the triggering of the whole structure of the new form of power over life: the biocapital. Biology, but a study of the life resumes and borrows the concept of Bios and a re-reading, proposes more than interpretations, determines prescriptions. The Bios on Biopolitics, biopower and biocapital is clinically prescribed life and governed by the order of the State. This does not mean that your life is fully protected. The state is crafty. Here the need to present a thesis in Volumes III. Each volume comes gradually, with the guiding principle cochlear implant, the evolution of biopolitics for biopower and bio-power to biocapital. As a result, deals with the construction of identities, graphics work, speech and language clinically created and circulated through the Ideological Apparatuses of the State. Their production reach the population, which it serves, on an industrial scale. It is also the subjectivity of the robotic body or electric-machinic human and ways how they relate to your community. It could not exploit size territory themes as contemporary problems caused by the production of clinical-discursive language, education and cultural identities by normal industry; film production and genetics, the secret of DNA speech, the human being as registration and the body as a product on the market - patents, series, models and the like between fiction and reality; about the mishaps caused by the use of technology in contemporary intraorgânica, empty speeches and cyborg subjectivity, were not deployed, each in separate volumes. At the same time, all subjects obey one didactic / methodological sequence which results in facilitating their understanding and correlations. Each volume depicts concomitant and / or episodes, although at different times, are interlaced by visuoimperceptual control proposal. However, it can read the volumes in a sequence and therefore the numbering contained in its pages follow a linear order. But you can read them separately, or read the volumes seeking information among them through signs marked in a few paragraphs. For example, the volume I can "jump" to Volume III and understanding on some issues in greater depth because all volumes are intended to communicate, soaking directions between the volumes are in the footer of your pages. Therefore, it is possible to make an immersive reading, not completely linear fashion in that the way it was thought the thesis, allows coming and going - in search of information - among volumes.